Growth and yield of tomatoes as influenced by different substrates, substrate volumes and irrigation frequencies - Ismail, Mohd Razi; Mohd Saud, Halimi; Jusoh, K. (International Society for Horticultural Science, 1993)
The effects of different substrates, substrate volumes and irrigation frequencies on the growth and yield of tomatoes were investigated. Highest leaf dry weight and yield were achieved when plants were grown in 6 litres sand culture irrigated 4–5 times daily. Utilizing soilless media improved root growth which contributed to efficiency in water and nutrient uptake. The importance of proper irrigation management was evident when there was a 70% reduction in overall yield with one and two compared to four or five irrigation daily. Leaf water potential, stomatal conductance and leaf photosynthesis were reduced when irrigated once daily in the morning.